Optical properties of BaTiO₃ at room temperature: DFT Modeling - Tolegen, Ulzhan (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2026)
The optical properties of the tetragonal phase of BaTiO₃ were investigated using density functional theory (DFT). To describe the static crystal lattice, the generalized gradient approximation with on-site Hubbard correlation (GGA+U) as well as a hybrid functional were employed. In order to account for the thermal motion of atoms, ab initio molecular dynamics calculations within the GGA+U framework were performed. Optical absorption spectra were calculated both for the static lattice and along the molecular dynamics trajectory. The obtained results demonstrate that consideration of atomic thermal motion leads to a significant reduction in the calculated optical absorption threshold energy. This effect can be explained by two main factors. First, changes in atomic configuration induced by thermal motion transform electronic transitions that are optically forbidden (dark) in the static lattice into optically allowed (bright) transitions. Second, the optical absorption edge is reduced due to fluctuations in the energies of electronic transitions caused by atomic motion. The calculations were performed separately for different k-points of the Brillouin zone.